Cardiomyopathies and the Armed Forces. Issue 3 (5th August 2015) - Holdsworth, D A; Cox, A T; Boos, C; Hardman, R; Sharma, S
Abstract : Cardiomyopathies are a group of heterogeneous myocardial diseases that are frequently inherited and are a recognised cause of premature sudden cardiac death in young individuals. Incomplete expressions of disease and the overlap with the physiological cardiac manifestations of regular intensive exercise create diagnostic challenges in young athletes and military recruits. Early identification is important because sudden death in the absence of prodromal symptoms is a common presentation, and there are several therapeutic strategies to minimise this risk. This paper examines the classification and clinical features of cardiomyopathies with specific reference to a military population and provides a detailed account of the optimum strategy for diagnosis, indications for specialist referral and specific guidance on the occupational significance of cardiomyopathy.